Musculoskeletal Tuberculosis - Indira Paramitha Maharani, Putu; Auliya Cahya Putri, Baiq; Annisa Rahmasita , Siti (Jurnal KESANS : Kesehatan dan Sains, 2021)
Tuberculosis (TB) remains the most common cause of death from infectious disease world-wide. In the UK, the incidence of TB has risen by 25% over the last 10 years; and almost one third of all case of tuberculosis are found in South East Asia. Extrapulmonary diagnosis remains challenging and can be delayed. This study evaluates the all aspect of musculoskeletal tuberculosis. To know an overview of general musculoskeletal tuberculosis; indentify the characteristic of patien with musculoskeletal tuberculosis; knowing the prevalance of musculoskeletal tuberculosis and how to treat musculoskeletal tuberculosis patien properly. This reserch use Literatur-Review method. Extra-pulmonary TB and is most often found in the spine, which is about 50% of all cases of tuberculosis of the musculoskeletal system. The common lesions in skeletal TB consist of osteomyelitis and arthritis. The most common signs and symptoms are spinal pain accompanied by weakness of the legs and neurological deficits. In addition, gibbus, swelling and limitation of motion in the joints can occur. Management in cases of musculoskeletal tuberculosis is treat the main etiologic in this case usually mycobacterium tuberculosis with anti-tuberculosis drug treatment